DAMPAK PARTISIPASI MASYARAKAT MENJAGA LINGKUNGAN DI PUSAT KOTA GARUT - Ikeu Kania (GoAcademica Research dan Publishing, 2018)
However, the IKLH's most dominant environmental concerns are to water quality degradation and plant cover. This research is centered on the environmental difficulties in Garut Regency, namely in Garut Kota's core, not only the rubbish that was spread after CFD activities ceased. For environmental issues to be handled, the government needs the public's help. In this study, Huraerah's notion of community involvement is applied. Description and qualitative technique are utilized in the study. As a consequence of this study, community engagement in Garut Kota's central business district is still very much needed but the most essential point is that community engagement in environmental protection is not only about how many people participate, but about protecting the environment itself.